Estimação de volumes de tráfego com base na morfologia urbana. Estudo de caso: cidade de Fortaleza-CE - Jales, Antônio Wagner Lopes (2009)
This paper presents an alternative methodological proposal for macroscopic modeling of traffic flows rates, considering the grid design as inductor of veicular flows, configuring a case study of the Daily Average Volumes of Fortaleza City, Ceará State. The tool called Space Syntax and one of its derivations called Angle Segments Analysis were used as a criterion of hierarchization of the streets. The values generated by such tool were used as input data as well as operational data of traffic were used for the construction of a training scheme for modeling through Artificial Neural Networks, and the values of Daily Average Volumes were used as output ones. The research aims at developing low cost method to preview volume flows and that could eliminate the need of numerous data required by the traditional UTMS modeling know as of four-stage model like for example, the survey origin / destination.